From Bactria to Taprobane : Selected Works of Osmund Bopearachchi. Volume II: Art History and Maritime Trade - Bopearachchi, Osmund, (Brill | Manohar Publishers & Distributors, 2015)
The second volume of Osmund Bopearachchi has articles and monographs on Central Asian and Indian art, South Indian and Sri Lankan art and finally maritime trade in the Indian Ocean. While documenting thousands of coins in the Pakistani markets from 1992 onwards, Bopearachchi realised that one has to go beyond the traditional approach of simply cataloguing coins, and as a result he has made an attempt to link numismatics with sculptural and pictorial iconography. His studies on Utpalavarnā, the courtesan who later became a bhiksunī (Buddhist nun) and on the earliest iconography of Hindu gods like Śiva, Brahmā, Vi]s]nu and Varāha have revolutionised our knowledge of these domains. His writings giving the results of the archaeological excavations and explorations carried out by the Department of Archaeology and the French Archaeological Mission in Sri Lanka along the estuaries and rivers provide substantial evidence to indicate that in ancient times large ships could cast anchor in the sea close to river mouths and commodities were taken to inland markets using the rivers and waterways. His work also shows how the movements caused by these human activities have amalgamated local traditions with foreign identities and created new forms of art and belief. His research on sculptures imported to the island from Amarāvatī-Nāgārjunakonda deals with the inspiration of these schools of art over the early forms of Buddhist sculpture in Sri Lanka. The different architectural aspects of the royal palace complex of Sigiriya, built by King Kassapa (477-95 CE) clearly demonstrate that various external ideas and concepts were used to convert this huge lofty rock into a more elaborate harmonious whole, in another words, a paradise or an Alakmanda.